A graphitic edge plane rich meso-porous carbon anode for alkaline water electrolysis - Shin, Dongyoon; Choun, Myounghoon; Ham, Hyung Chul; Lee, Jae Kwang; Lee, Jaeyoung (ROYAL SOC CHEMISTRY, 2017)
There is growing interest in alkaline water electrolysis as a sustainable approach for producing hydrogen, but developing efficient and inexpensive catalysts for the oxygen evolution reaction, which can limit the operational efficiency of water electrolysis due to its considerable overpotential, is regarded as the most overriding challenge. Therefore, significant progress has been made in developing catalysts with transition metal and carbon materials as alternative catalysts. Here, we prepared cobalt containing carbon nanofibers via a facile route of electrospinning and pyrolysis, and metal leached carbon nanofibers were also prepared by subsequently leaching the metal. Despite metal leaching, the latter ones still show comparable activity and stability with iridium black in alkaline water electrolysis. After detailed physicochemical and electrochemical characterizations, we revealed that graphitic edge plane rich carbon is mainly responsible for the activity of our material rather than embedded metal species. In addition, the metal plays a role in forming the specific carbon structure along with improving graphitization based on the catalytic graphitization. This result indicates the importance of the graphitic edge plane and might be helpful to understand carbon anodes for alkaline water electrolysis.
Keywords: OXYGEN REDUCTION REACTION; N-DOPED GRAPHENE; METAL-FREE; EVOLUTION REACTION; NITROGEN; IRON; ELECTROCATALYST; NANOPARTICLES; CATALYSTS; NANOFIBER